SCIENCE TEACHING AND LEARNING THROUGH KATH MURDOCH’S INQUIRY CYCLE: A CASE STUDY ON PRESERVICE PRIMARY TEACHERS - Bertha Natalina Silitonga; Wiyun Tangkin (Universitas Pelita Harapan, 2023)
Abstract Many studies on inquiry focus on the effect of inquiry learning on students' learning abilities and science skills. However, research focusing on the learning experience and teaching skills of preservice teachers based on inquiry is still lacking. The practices that a preservice teacher undertakes in his/her teaching years are strongly influenced by his/her learning experience in teacher education. The inquiry learning experienced by preservice teachers while in college will later affect inquiry-based teaching practiced in schools. This qualitative research aims to describe inquiry practices conducted by pre-service teachers. The sample of the study was 33 preservice primary teachers who took the second-year science content course named Integrated Science for Primary. There are two questions that will be the focus of this research: 1) How does Kath Murdoch’s Inquiry Cycle help preservice teachers experience significant learning? 2) How does an inquiry cycle help preservice teachers design Inquiry-based Science Lesson Plan? This study shows that learning through Kath Murdoch’s inquiry cycle is found as an interesting and useful approach for preservice teachers to understand how scientific processes are integrated into their experiment designs. Also, an inquiry cycle used in guided practices (including metacognitive prompts, reflections, and group discussion) could provide preservice teachers with the necessary skills to develop an inquiry-based teaching plan. Yet, this does not guarantee that preservice teachers would successfully facilitate inquiry in a real classroom setting. Bahasa Indonesia AbstrakBanyak penelitian tentang inkuiri berfokus pada pengaruh pembelajaran inkuiri terhadap kemampuan belajar siswa dan keterampilan sains. Namun, penelitian yang berfokus pada pengalaman belajar dan keterampilan mengajar calon guru yang berbasis inkuiri masih sedikit. Praktik yang dilakukan seorang calon guru di tahun-tahun mengajarnya sangat dipengaruhi oleh pengalaman belajarnya selama di pendidikan keguruan. Pembelajaran inkuiri yang dialami oleh calon guru selama di bangku kuliah nantinya akan mempengaruhi pengajaran berbasis inkuiri yang dipraktikkan di sekolah. Penelitian kualitatif ini bertujuan untuk mendeskripsikan praktik inkuiri yang dilakukan oleh calon guru. Sampel penelitian adalah 33 calon guru SD yang mengambil mata kuliah konten sains tahun kedua yaitu IPA Terpadu untuk Sekolah Dasar. Ada dua pertanyaan yang akan menjadi fokus penelitian ini: 1) Bagaimana Siklus Inkuiri Kath Murdoch membantu calon guru mengalami pembelajaran yang signifikan?; 2) Bagaimana siklus inkuiri membantu calon guru merancang Rencana Pembelajaran IPA berbasis Inkuiri? Studi ini menunjukkan bahwa pembelajaran melalui siklus Kath Murdoch adalah pendekatan yang menarik dan berguna bagi calon guru untuk memahami bagaimana proses ilmiah diintegrasikan ke dalam rancangan eksperimen. Juga, siklus inkuiri yang digunakan dalam praktik terbimbing (termasuk petunjuk metakognitif, refleksi, dan diskusi kelompok) dapat memperlengkapi calon guru dengan keterampilan yang diperlukan untuk mengembangkan rencana pengajaran berbasis inkuiri. Namun, ini tidak menjamin bahwa kelak calon guru tersebut akan berhasil memfasilitasi praktik inkuiri di kelas nyata.